SOSIALISASI PENYAKIT CACING PITA DAGING BABI DAN BEBERASAN PADA MASYARAKAT DI DESA BINAAN UNUD, DESA TIANYAR BARAT, KARANGASEM - N.S, Dharmawan; Damriyasa, I M.; Oka, I. B.M.; Agustina, I K. K.; Swacita, I. B. N.; Mahardika, I G. (Buletin Udayana Mengabdi, 2013)
This Community Service was conducted on August 5th, 2012 in Tianyar Barat village, Karangasem regency in the form of socialization of taeniosis and cysticercosis on the local community leaders. The aim of this program was to give knowledge, clinical symptoms, transmission, and prevention of the taeniosis and cysticercosis. There were 37 participants who come from representatives of each area. Twenty-seven (72.9%) participants reported that at their house they raise pigs, and 11 out of 27 (40.7%) participants reported that the pigs are traditionally rearing raised without a confinement fence. Free-range pig husbandry system was important risk factors for pig cysticercosis. The activity run smoothly as planned. Socialization of these zoonotic diseases has improved the understanding of all participants. At the end of the activity, all of them (100%) reported that they were satisfied; and all of them (100%) also are interested in becoming a volunteer to joint to inform the diseases to other people.